Invasive pathogens impacting forest and urban trees in Türkiye - Tuğba Doğmuş Lehtijarvi; Stephen Woodward (Turkish Journal of Forestry, 2024)
Alien invasive pests and pathogens pose major threats to forest and ornamental trees throughout the world. The history of invasions is reviewed in the context of human migrations in the past, and the importance of modern globalization of trade – in the absence of highly stringent detection and control measures - emphasised as undoubtedly the most important cause of the recent upsurge in incursions of problematic pests and pathogens. Examples of invasive pathogens, including the causes of sweet chestnut canker, Dutch elm disease, dieback of Cupressus, Phytophthora root rots, boxwood blight, canker stain (wilt) of Platanus and Dothistroma needle blight of pines are detailed. Measures taken by states and trading blocks to reduce the probabilities of invasions occurring and manage those that have already occurred are discussed, along with approaches that could be utilized to improve the protocols used to address these problems in Türkiye.